Use of Tobacco and Tobacco Products By Public Employees in Konya Province and the Support Status of the Tobacco Control Law - Kutlu, Ruhuşen; Marakoğlu, Kamile; Demirbaş, Nur; Yeşildağ, Kerim; Çavdarcı, Ferahnur (Addicta: The Turkish Journal on Addictions, 2021)
This study aimed to evaluate the frequency of the use of tobacco and tobacco products among public employees in Konya province and support for the tobacco control law. This cross-sectional, analytical study was carried out on 4,874 public employees. The participants were surveyed about the use of tobacco and tobacco products, the tobacco control law, and smoking ban in closed areas. Of the participants, 59.7% were current and/or occasional users of various tobacco products. Specifically, 36.5% of the participants were current smokers. Men smoked 2,272 times more than women (p
Keywords: Public employees; tobacco and tobacco products; tobacco control law